Pengaruh Cekaman Salinitas terhadap Pertumbuhan Tanaman Semusim - Tambun Sihotang (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2021)
The purpose of the implementation of this practicum is to find out the effect of salinity checks on the growth of several plants a season.  This experiment was conducted at the Plant Ecology Laboratory Agroecotechnology Study Program of the Faculty of Agriculture, University of North Sumatra, Medan on 21 April 2016 until May 19, 2016 at an altitude of 25 meters above sea level.  This experiment was conducted using the factorial RandomIzed Design Method (RAK) with 2 factors, namely: Factor 1: Commodity (K) Level: K1 = Kale, K2 = Mustard; K3 = Green Beans; K4 = Corn, Factor 2: Salinity Level (S) Level: S0 = Control; S1 = Low; S2 = Medium; S3 = Height.  The parameters observed are plant height (cm); number of leaves (strands); root volume (m3); root length (cm; wet weight of roots and headers; harvesting.  From the results of the experiment it was obtained that the salinity level affected all parameters.